Analisis Yuridis Terhadap Bentuk Perubahan Status Tanah Menjadi Hutan Lindung (Studi Penelitian di Kabupaten Bintan) - Dheavani Afrila; Soerya Respationo; Muhammad Tartib; Erniyanti Erniyanti (UNES Law Review, 2023)
This research uses normative research methods supported by empirical research. By examining the positive laws that apply in Indonesia and analyzing data obtained directly from the field or facts that occur in society. Aims to find out how the legal regulations, implementation and factors that become obstacles/obstacles and solutions to the change in land status to protected forest occur (Research Study in Bintan Regency). The research results show that legal arrangements occurred due to the issuance of the Decree of the Minister of Forestry Number: 173/KPTS-II/1986 dated 06 June 1986 concerning the Designation of forest areas in the Dati I Riau Province Region as Forest Areas, concerning Forestry Implementation. However, in practice, there are still many who do not know how changes in land status can occur. Researchers hope that there will be knowledge of justice for the parties. So as not to create legal uncertainty in implementing law in Indonesia.